2015
DOI: 10.1007/s11104-015-2686-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of the fine root production, phenology, and turnover rate of six shrub species from a subtropical forest to a soil moisture gradient and shading

Abstract: Background and aims Knowledge of the fine root dynamics of different life forms in forest ecosystems is critical to understanding how the overall belowground carbon cycling is affected by climate change. However, our current knowledge regarding how endogenous or exogenous factors regulate the root dynamics of understory vegetation is limited. The aims of this study were to test the effects of soil moisture gradient and shading on the fine root production, phenology, and turnover rate of six shrub species from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Different RTRs also resulted from different dominant species (Tables 1 and 5). For example, it has been reported that forest and tundra RTR variations depend on site-specific species [75,76]. Our results showed there were no significant differences in AMS and AS with respect to similar dominant species (S. purpurea) in this study (Table 1).…”
Section: Root Turnover Ratescontrasting
confidence: 38%
“…Different RTRs also resulted from different dominant species (Tables 1 and 5). For example, it has been reported that forest and tundra RTR variations depend on site-specific species [75,76]. Our results showed there were no significant differences in AMS and AS with respect to similar dominant species (S. purpurea) in this study (Table 1).…”
Section: Root Turnover Ratescontrasting
confidence: 38%
“…In nutrient-rich soil, root retention cost can be more than the formation of new roots (Aragao et al, 2009) decaying FR, while in AH system, the slow turnover rate indicated the decreased requirement of carbon for new rood production. Low precipitation creates a water-limited climate for plants and thus results in a powerful response in terms of FRP (Fu et al, 2015). Graefe et al (2008a), Graefe et al (2008b), stated that root growth of the trees is stimulated by higher water availability and seems to act as a second controlling factor after temperature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, root growth was greater in the dry than in the wet season in an eastern Amazonian forest, because of the lower water availability (Lima et al, 2010). Changing water availability can also affect the peaks and amounts of root growth of understory shrub species in subtropical forests with seasonal droughts (Fu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%